Analisis kontribusi komitmen organisasi, motivasi kerja, dan kepuasan kerja terhadap produktivitas Guru PPKn SMP di Kabupaten Purworejo - Patniwati, Patniwati (Journal of Education Policy and Management Studies, 2024)
Abstract: Teacher productivity is an important element in the success of education, especially in supporting the achievement of educational goals.  In the context of work productivity, organisational commitment, work motivation, and job satisfaction are three factors that are interrelated and influence directly or indirectly. This study aims to analyse the contribution of organisational commitment, work motivation and job satisfaction to the work productivity of junior high school Civics teachers in Purworejo Regency. (2) Analyse the contribution of organisational commitment to the work productivity of junior high school Civics teachers in Purworejo Regency. (3) Analyse the contribution of work motivation to the work productivity of junior high school Civics teachers in Purworejo Regency. (4) Analysing the contribution of job satisfaction to the work productivity of junior high school Civics teachers in Purworejo Regency. This type of research is quantitative research. The variables in this study are organisational commitment, work motivation, job satisfaction and teacher work productivity. The population of this research is census research/saturated sampling/total sampling, so that all Civics teachers who teach at junior high schools in Purworejo Regency are used as research samples, namely 104 teachers. The data collection technique used a questionnaire. The analysis used is multiple linear regression analysis. Based on the results of data analysis, the conclusions are obtained: (1) Organisational commitment, work motivation and job satisfaction contribute significantly to the work effectiveness of junior high school Civics teachers in Purworejo Regency. Positive and significant means that the better the organisational commitment, work motivation and job satisfaction, the teacher's work productivity will also be good (2) Organisational commitment contributes significantly to the work effectiveness of junior high school Civics teachers in Purworejo Regency. Positive and significant means that the better the organisational commitment, the teacher's work productivity will also be good, (3) Work motivation contributes significantly to the work effectiveness of junior high school Civics teachers in Purworejo Regency. Positive and significant means that the better the work motivation, the teacher's work productivity will also be good, (4) Job satisfaction contributes positively and significantly to the work effectiveness of junior high school Civics teachers in Purworejo Regency. Positive and significant means that the better the job satisfaction, the better the teacher's work productivity. Abstrak: Produktivitas guru merupakan elemen penting dalam keberhasilan pendidikan, terutama dalam mendukung tercapainya tujuan pendidikan  Dalam konteks produktivitas kerja, commitment organisasi, motivasi kerja, dan kepuasan kerja merupakan tiga faktor yang saling berkaitan dan berpengaruh secara langsung maupun tidak langsung penelitian ini bertujuan untuk Menganalisis kontribusi komitmen organisasi, motivasi kerja dan kepuasan kerja terhadap produktivitas kerja guru PPKn SMP Se-Kabupaten Purworejo. (2) Menganalisis kontribusi komitmen organisasi terhadap produktivitas kerja guru PPKn SMP Se-Kabupaten Purworejo. (3) Menganalisis kontribusi motivasi kerja terhadap produktivitas kerja guru PPKn SMP Se-Kabupaten Purworejo. (4) Menganalisis kontribusi kepuasan kerja terhadap produktivitas kerja guru PPKn SMP Se-Kabupaten Purworejo. Jenis penelitian ini adalah penelitian kuantitatif. Variabel dalam penelitian ini adalah komitmen organisasi, motivasi kerja, kepuasan kerja dan produktivitas kerja guru. Populasi penelitian ini adalah penelitian sensus/sampling jenuh/total sampling, sehingga seluruh guru mata pelajaran PPKn yang mengajar pada SMP di Kabupaten Purworejo dijadikan sampel penelitian yaitu 104 guru. Teknik pengambilan data menggunakan angket. Analisis yang digunakan adalah analisa regresi linear berganda. Berdasarkan hasil analisis data maka diperoleh kesimpulan: (1) Komitmen organisasi, motivasi kerja dan kepuasan kerja berkontribusi positif secara signifikan terhadap efektifitas kerja guru PPKn SMP Se-Kabupaten Purworejo. Positif dan signifikan artinya semakin baik komitmen organisasi, motivasi kerja dan kepuasan kerja maka produktivitas kerja guru juga akan baik (2) Komitmen organisasi berkontribusi positif secara signifikan terhadap efektifitas kerja guru PPKn SMP Se-Kabupaten Purworejo. Positif dan signifikan artinya semakin baik komitmen organisasi maka produktivitas kerja guru juga akan baik, (3) Motivasi kerja berkontribusi positif secara signifikan terhadap efektifitas kerja guru PPKn SMP Se-Kabupaten Purworejo. Positif dan signifikan artinya semakin baik motivasi kerja maka produktivitas kerja guru juga akan baik, (4) Kepuasan kerja berkontribusi positif secara signifikan terhadap efektifitas kerja guru PPKn SMP Se-Kabupaten Purworejo.. Positif dan signifikan artinya semakin baik kepuasan kerja maka produktivitas kerja guru juga akan baik.